Prediction of time to exhaustion in competitive cyclists from a perceptually based scale - Garcin, M.; Coquart, J. B. J.; Robin, S.; Matran, R. (The Journal of Strength and Conditioning Research, 2011)
Prediction of time to exhaustion in competitive cyclists from a perceptually based scale. We have tested the validity of the estimated time limit (ETL) scale to predict an exhaustion time (Tlim) from values stemming from incremental and randomized constant workloads tests on a cycle ergometer. Twenty-five cyclists performed 1 continuous incremental test, 1 discontinuous test with randomized workloads, and 1 constant power output test at 90% of maximal aerobic power (MAP) to exhaustion. Estimated time limits at 90% MAP during the incremental test and the test with randomized workloads were calculated from exponential relationships between power and ETL using the same 4 workloads. Real measured Tlim during the constant power output test was converted into ETL values (called measured ETL). The differences between the calculated and measured ETLs were examined. Estimated time limits calculated at 90% MAP during the incremental and randomized tests corresponded to 14 minutes 56 seconds and 10 minutes 14 seconds, whereas measured ETL was equal to 11 minutes 19 seconds ± 3 minutes 40 seconds. The results showed a nonsignificant difference between calculated and measured ETLs. However, the mean differences between the measured ETL values during the constant test performed at the same intensity were -1.3 ± 2.9 and 0.3 ± 3.0 for the incremental and the randomized constant workloads tests, respectively. Consequently, the use of ETL calculated at 90% MAP during the test with randomized constant workloads may be preferable to predict the accurate Tlim. Moreover, it would seem that high-level cyclists, who were more consciously attuned to their bodies and their own effort sense, were more accurate in their prediction than low-level cyclists. It is concluded that the randomized constant workloads test that is both shorter and less strenuous would be more convenient for high-level athletes.